2020
DOI: 10.3390/su12041364
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges for Hurricane Resilience on Agricultural and Forest Land in the U.S. Southeast and Caribbean

Abstract: Three storms in the 2017 hurricane season caused $265 billion in damages in the U.S. Southeast and Caribbean, including billions in losses in the agriculture and forestry sector. Climate change projections indicate that such disastrous hurricane seasons are becoming more normal. Working land management sectors need to prepare for this future. However, few studies evaluate hurricane resilience strategies, or challenges faced by land managers surrounding hurricane events. Boundary organizations are critical to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The southeastern United States has a generally warm, moist climate with enormous natural potential for plant and animal production (Fike et al., 2006; Franzluebbers, 2005). The climatic conditions can also be very harsh, with (a) long, hot summers that challenge plant productivity during critical growth periods, (b) hurricanes that can overwhelm crop and livestock enterprises with excessive rainfall and high winds, (c) high humidity that can facilitate widespread plant disease infections and limit safe storage of agricultural products, (d) intense thunderstorms that can wash away layers of precious topsoil within an afternoon, and (e) persistent winter precipitation that can leach available nutrients from soil (Afroz et al., 2021; Cammarano & Tian, 2018; Kunkel et al., 2013; Pathak et al., 2012; Wiener et al., 2020). These challenges could be at least partially addressed with management practices such as conservation tillage and cover cropping to protect the soil surface from erosion, restore soil fertility through organic matter cycling, improve soil health via habitat enhancement, and mitigate greenhouse gas emissions through soil C accumulation and enhanced fertilizer use efficiency (Franzluebbers, 2010; Lal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The southeastern United States has a generally warm, moist climate with enormous natural potential for plant and animal production (Fike et al., 2006; Franzluebbers, 2005). The climatic conditions can also be very harsh, with (a) long, hot summers that challenge plant productivity during critical growth periods, (b) hurricanes that can overwhelm crop and livestock enterprises with excessive rainfall and high winds, (c) high humidity that can facilitate widespread plant disease infections and limit safe storage of agricultural products, (d) intense thunderstorms that can wash away layers of precious topsoil within an afternoon, and (e) persistent winter precipitation that can leach available nutrients from soil (Afroz et al., 2021; Cammarano & Tian, 2018; Kunkel et al., 2013; Pathak et al., 2012; Wiener et al., 2020). These challenges could be at least partially addressed with management practices such as conservation tillage and cover cropping to protect the soil surface from erosion, restore soil fertility through organic matter cycling, improve soil health via habitat enhancement, and mitigate greenhouse gas emissions through soil C accumulation and enhanced fertilizer use efficiency (Franzluebbers, 2010; Lal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Solo el huracán María en 2017 causó más de $2,300 millones de dólares (en dólares de 2022) en pérdidas y daños a cultivos e infraestructuras 169 , lo que representó una reducción de alrededor el 80 % del valor agrícola total de la isla principal 170 . Más allá de estos impactos directos, una parte sustancial de las pérdidas agrícolas fue causada por los efectos indirectos de los ciclones tropicales, incluidos los cortes de energía, la interrupción de las telecomunicaciones y del suministro de agua y las carreteras y los sistemas de riego dañados 152,168,171 . Con el aumento proyectado de la intensidad de los grandes ciclones tropicales, se espera que estos impactos empeoren si no se realizan inversiones para que los sistemas alimentarios e hídricos sean más resilientes (KM 8.3, 11.3, 30.1).…”
Section: Factores De Estrés Climático En Los Componentes De Los Siste...unclassified
“…While participation in insurance and conservation programs both reflect producers' desire to invest in loss mitigation, integrating efforts to prevent or mitigate future disaster impacts into post‐disaster recovery programming could help to build a longer term iterative approach. Numerous examples in the literature (Chatrchyan et al, 2017; Wiener et al, 2020; Wreford et al, 2017) have indicated that farmers who have recently experienced extreme events are more likely to be motivated to take adaptive actions in anticipation of future extreme events. Accordingly, the aftermath of a major disaster could provide an opportunity to promote adaptation and mitigation strategies.…”
Section: New Approaches For Improved Farm‐level Resiliencementioning
confidence: 99%